Implementation of the Planned Hijrah Savings Program (tabura) to Increase the interest of Prospective Pilgrims during the Covid-19 Pandemic at Persada Indonesia Hajj and Umrah Travel in Surabaya - Mayan Fauni, Arini; Bramayudha, Airlangga (Proceedings of International Conference on Da'wa and Communication, 2021)
This study aims to describe the Implementation of the TABURA program at Persada Indonesia to increase the interest of prospective pilgrims during the COVID-19 pandemic. Then this study also aims to find out several factors that support and hinder the TABURA program to increase the interest of prospective Umrah pilgrims during the COVID-19 pandemic. In conducting this research, researchers used qualitative research methods with descriptive research types. Data collection techniques are used by researchers in searching for data in the form of field observations, interviews with several sources, and documentation. Researchers used the Data Triangulation technique to validate the data by cross-checking data, time, and sources. The results obtained by researchers illustrate that the TABURA program can increase the interest of prospective pilgrims. During the year this program has been running, up to 200 people have registered. While the supporting factors for this program are a flexible system and the opportunities this program has are the significant market share and alumni. While the weakness of this program is the unstable economy, the threats that arise are government policies that are not yet concrete and uncertain.